2015
DOI: 10.1002/jor.22998
|View full text |Cite
|
Sign up to set email alerts
|

Osteochondral allograft transplantation in cartilage repair: Graft storage paradigm, translational models, and clinical applications

Abstract: The treatment of articular cartilage injury and disease has become an increasingly relevant part of orthopaedic care. Articular cartilage transplantation, in the form of osteochondral allografting, is one of the most established techniques for restoration of articular cartilage. Our research efforts over the last two decades have supported the transformation of this procedure from experimental “niche” status to a cornerstone of orthopaedic practice. In this Kappa Delta paper, we describe our translational and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
117
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 109 publications
(125 citation statements)
references
References 47 publications
(88 reference statements)
3
117
1
Order By: Relevance
“…To the authors knowledge, this is the first report of PEMF for improved engineered cartilage growth and integration, both in vitro and in vivo. Devitalized bone bases did not elicit an immunogenic response in biocompatibility tests (data not shown), and we anticipate that engineered cartilage is analogous to allogeneic cartilage allografts, which have been used clinically for decades and not thought to pose a significant immunogenic risk (Bugbee et al, 2016). This preliminary in vivo experiment was potentially limited by sample size, which was improved by creating multiple defects per knee.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…To the authors knowledge, this is the first report of PEMF for improved engineered cartilage growth and integration, both in vitro and in vivo. Devitalized bone bases did not elicit an immunogenic response in biocompatibility tests (data not shown), and we anticipate that engineered cartilage is analogous to allogeneic cartilage allografts, which have been used clinically for decades and not thought to pose a significant immunogenic risk (Bugbee et al, 2016). This preliminary in vivo experiment was potentially limited by sample size, which was improved by creating multiple defects per knee.…”
Section: Discussionmentioning
confidence: 97%
“…It has been reported that approximately 60% of knee arthroscopies find chondral lesions, 67% of which can be categorized as focal defects (Widuchowski, Widuchowski, & Trzaska, 2007). Cartilage repair and restoration surgeries, such as microfracture (MF), osteochondral autograft transfer (OAT), osteochondral allograft (OCA), and cell‐culture techniques (i.e., autologous chondrocyte implantation) are each limited by a number of factors, including availability of graft tissue, donor site morbidity, and difficulty in matching size and surface contours (Bugbee, Pallante‐Kichura, Görtz, Amiel, & Sah, 2016; Nover et al, 2015). In attempts to overcome some of these issues, a number of engineered cartilage technologies are progressing through the clinical pipeline (Iwasa, Engebretsen, Shima, & Ochi, 2009; Pietschmann et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therapies for restoring normal knee function through the regeneration of articular cartilage have been investigated (Mardones, Jofré, & Minguell, ), but the development of an effective treatment for OA is still a work in progress. To date, bone marrow‐stimulation techniques (Erggelet & Vavken, ); autologous and allogeneic osteochondral grafts (Bugbee, Pallante‐Kichura, Görtz, Amiel, & Sah, ; Hangody & Füles, ); and autologous chondrocyte implantation (Brittberg et al, ; Clavé et al, ; Tohyama et al, ) have been used for the treatment of relatively small cartilage defects. The clinical outcomes so far suggest some success, but evidence is inconclusive, and there are concerns about repair with fibrocartilage and donor site morbidity (Matricali, Dereymaeker, & Luyten, ).…”
Section: Introductionmentioning
confidence: 99%
“…The viability of chondrocytes within the graft remains at acceptable levels for ;28 days (46). OCA transplantation is an extension of the OAT technique but harvests grafts from donated knee joints rather than using the patient's own tissue, thus eliminating donor-site morbidity.…”
Section: Osteochondral Techniquesmentioning
confidence: 99%